2016
DOI: 10.1177/1359105316639436
|View full text |Cite
|
Sign up to set email alerts
|

‘Strong is the new skinny’: A content analysis of #fitspiration images on Instagram

Abstract: 'Fitspiration' is an online trend designed to inspire viewers towards a healthier lifestyle by promoting exercise and healthy food. This study provides a content analysis of fitspiration imagery on the social networking site Instagram. A set of 600 images were coded for body type, activity, objectification and textual elements. Results showed that the majority of images of women contained only one body type: thin and toned. In addition, most images contained objectifying elements. Accordingly, while fitspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
318
2
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(387 citation statements)
references
References 28 publications
(40 reference statements)
19
318
2
20
Order By: Relevance
“…The issues of frustration, guilt and feeling addicted to viewing Fitspirational posts are novel insights emerging from the current study. Negative effects of exposure to Fitspiration on self-esteem, body image and disordered eating have been demonstrated [3] and speculated upon [7][8][9][10][11][12][13] previously and the accounts of our participants are in line with these studies and also the proposition that social comparison on the basis of appearance is one of the routes by which Fitspiration produces negative psychological effects [3].…”
Section: Discussion Key Findingssupporting
confidence: 83%
See 2 more Smart Citations
“…The issues of frustration, guilt and feeling addicted to viewing Fitspirational posts are novel insights emerging from the current study. Negative effects of exposure to Fitspiration on self-esteem, body image and disordered eating have been demonstrated [3] and speculated upon [7][8][9][10][11][12][13] previously and the accounts of our participants are in line with these studies and also the proposition that social comparison on the basis of appearance is one of the routes by which Fitspiration produces negative psychological effects [3].…”
Section: Discussion Key Findingssupporting
confidence: 83%
“…In line with Palmer [14] we found that participants described desire to gain information as a key driver of consumption of Fitspirational material; specifically, our participants were interested in information that would help them to improve their appearance, with health appearing a less important motivation. Similar to Tiggeman & Ziccardo [7] we also showed that participants could feel inspired and motivated by Fitspirational content. However, our findings showed that this does not seem to routinely translate into positive dietary change and physical activity; a finding also reported by Palmer [14].…”
Section: Discussion Key Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…Estudos apontam para a falta de diversidade de corpos como referencial de beleza, parecendo haver somente um modelo do que é belo e dificuldade em lidar com o diferente. Todos desejam ser iguais, como um pré-requisito para ser aceito, sendo o culto à magreza uma norma social, expondo-se à exclusão quem não adere a esse modelo 4,15,26 . A mídia atua reforçando e popularizando maneiras de se atingir o "corpo ideal".…”
Section: Discussionunclassified
“…Essas novas mídias reforçam o narcisismo e os padrões de beleza vigentes e alguns estudos avaliaram seu impacto sobre a imagem corporal (IC) 4,5 . A IC pode ser definida como a imagem do corpo construí-da em nossa mente e os sentimentos, pensamentos e ações em relação ao corpo 6 .…”
Section: Introductionunclassified